Editor' introduction: sharing borders - Quayum, Mohammad Abdul (Singapore National Library Board and Singapore National Arts Council, 2009)
An editor's introduction for the collection of critical essays on Malaysian-Singaporean Literature entitled, Sharing Borders: Studies in Contemporary Singaporean-Malaysian Literature